Efficacy of Aloe vera (Aloe barbadensis Miller) Gel Edible Coatings on Quality Characteristics of Tomato Fruit During Postharvest Storage: Aloe vera Coating on Tomato Fruit - Fareed Ahmed; Asadullah Marri; Khalil Ahmed Solangi; Nida Shaikh; Asif Irshad (Biological Sciences - PJSIR, 2025)
Tomato fruit is prone to perishability with a shorter shelf-life owing to higher moisture content. The technique of coating edible Aloe vera (AV) gel on tomato fruit proposes the prospect of adding an antioxidant rich un-conventional ingredient in culinary applications alongside an extension of the shelf life of fruit to minimize its commercial losses. The present study investigated the efficacy of Aloe vera (Aloe barbadensis Miller) gel coatings in extending the physiological shelf life of tomato fruit during twenty one days of storage at ambient temperature (24 °C ± 2). A total of three (03) Aloe vera gel concentrations i.e., 3, 6 and 9% were prepared and assessed for coating quality characteristics i.e., pH, total solids %, viscosity (cp), drying time (min) and coating weight (g). Moreover, AV gel concentrations were coated on tomato fruits to examine postharvest quality characteristics i.e., decay %, pH value, total soluble solids (TSS), titratable acidity %, sugar-acid (SA) ratio, weight loss %, moisture %, ash %, fibre %, carbohydrate % and vitamin C mg/100g after an interval of every 07 days during the storage period however uncoated tomato fruits were served as control. The results revealed that AV gel concentrations showed significant differences (P < 0.05) in coating quality characteristics. Results further revealed that tomato fruits coated with 6% AV gel maintained postharvest quality characteristics followed by 9% and 3% AV gel. It was further noticed that tomato fruits coated with AV gel notably maintained postharvest quality characteristics during the storage period in comparison to uncoated (control) fruits. The overall findings suggest that using 6% AV gel as edible coatings at ambient temperature (24 °C ± 2) may delay fruit ripening and extend the storage life of tomato fruit.